Microstructure, crystallinity and composition of alkali-silica reaction products in concrete determined by transmission electron microscopy. (April 2020) - Boehm-Courjault, E.; Barbotin, S.; Leemann, A.; Scrivener, K.
Abstract: Several aspects of alkali-silica reaction (ASR) are still poorly understood, for example the formation of ASR products occurring before significant aggregate cracking. This study focuses on the analysis of these products and the comparison with the products formed after crack formation. A novel approach for the characterisation of ASR products was used combining different electron microscopy techniques. This combination allows analysis of the ASR products present in small gaps and cracks with a width below 1 μm present between adjacent mineral grains of aggregates. In the three samples studied, the products in thin grain boundaries show no distinct morphology and they are amorphous. They were defined as untextured ASR products. The products present in larger veins form fibrils and platelets, called platey products, and are mainly crystalline. In spite of the differences in morphology, untextured and platey ASR products are of similar composition.